TINGKAT PENCAPAIAN KOMPETENSI MAHASISWA PROGRAM PROFESI DOKTER DI FAKULTAS KEDOKTERAN UNIVERSITAS PATTIMURA - Johan Bruiyf Bension; Samuel Maruanaya; Laura Bianca Sylvia Huwae; Stazia Noija (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Clinical education constitutes a crucial phase in the development of professional competence among medical students. Evaluating the level of competency achievement during the clerkship phase is essential to ensure that the implementation of clinical education aligns with the Standa Kompetensi Dokter Indonesia (SKDI). This study aimed to assess the level of medical competency achievement among clerkship students at the Faculty of Medicine, Universitas Pattimura (FK UNPATTI).A descriptive quantitative study with a cross-sectional design was conducted involving 171 clerkship students who had completed clinical rotations in the Departments of Obstetrics and Gynecology, Psychiatry, Ophthalmology, Otorhinolaryngology–Head and Neck, and Neurology in September 2024. Data were collected using a structured questionnaire based on the SKDI 2012 disease list and competency levels, employing a 1–5 frequency scale. Data analysis was performed using Microsoft Excel.The results showed that most respondents were from the 2018 batch (39.2%). The majority achieved competencies at level 3 (diagnosing, performing initial management, and referring) and level 4 (diagnosing and managing independently). The most frequently encountered cases included normal pregnancy (82.5%), tension headache, insomnia, and acute otitis media, whereas the least encountered cases were neurogenic bladder and complete spinal transaction.In conclusion, the overall competency achievement among FK UNPATTI clerkship students is satisfactory. These findings indicate that the clinical learning environment effectively supports the acquisition and consolidation of professional competencies among medical students.Keywords: medical competency, clinical education, SKDI, clerkship students